An investigation of the combined use of cation exchange enrichment and spectrochemical analysis for the determination of trace constituents in common silicate rocks and chondrites - Edge, Robert Arthur (Department of Geological Sciences, 2016)
The combined use of cation exchange enrichment and spectrochemical analysis has been investigated for determining trace constituents (particularly caesium and the rare earths) in common igneous rocks and chondritos. Cation exchange chromatography with hydrochloric acid elution was employed to resolve the complex mixtures obtained from rocks and meteorites into a number of fractions in which the concentration of various trace constituents were above their spectrochemical detection limits; the trace constituents are not required in a highly concentrated form. These elements may then be determined spectrochemically. Before developing suitable column procedures for the enrichment of trace constituents, the sequence with which both major and trace constituents of common igneous rooks and chondrites moved through cation exchange columns on elution with various concentrations of HCl were established. Perchloric acid was also investigated as an eluant. The spectrograph was used to monitor the effluent fractions obtained from the cation exchange columns. Suitable column conditions were then developed for concentrating several trace elements for spectrochemical analysis.